2006
DOI: 10.1007/s00268-005-0354-9
|View full text |Cite
|
Sign up to set email alerts
|

Is Surgery Beneficial for MEN1 Patients with Small (≤2 cm), Nonfunctioning Pancreaticoduodenal Endocrine Tumor? An Analysis of 65 Patients from the GTE

Abstract: This study suggests that surgery may not be beneficial for MEN1 patients with NFPET < or = 2 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
148
0
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(161 citation statements)
references
References 32 publications
4
148
0
9
Order By: Relevance
“…For this reason, for patients with MEN1 affected by pancreatic NETs !2 cm, a careful watching policy is recommended. In these patients, it seems advisable to perform a yearly follow-up with a prompt indication for surgery when tumor diameter growth O5 mm/year (89). Surgical treatment of gastrinomas in MEN1 patients is still debated (90).…”
Section: Surgery Of Nets In Multiple Endocrine Neoplasia Type 1 Patientsmentioning
confidence: 99%
“…For this reason, for patients with MEN1 affected by pancreatic NETs !2 cm, a careful watching policy is recommended. In these patients, it seems advisable to perform a yearly follow-up with a prompt indication for surgery when tumor diameter growth O5 mm/year (89). Surgical treatment of gastrinomas in MEN1 patients is still debated (90).…”
Section: Surgery Of Nets In Multiple Endocrine Neoplasia Type 1 Patientsmentioning
confidence: 99%
“…The peculiarity of the case besides surgical intervention was represented by pathological outcome, which identified the tumor as benign although it exceeded 2 cm. This comes in opposition with the WHO 2010 classification criteria that also claim that a neoplasm which has dimensions greater than 2 cm is considered to have a malignant development [11]. Systemic chemotherapy and radiation therapy have a limited effect on disease progression.…”
Section: Discussionmentioning
confidence: 65%
“…Several studies have suggested that larger tumors are more aggressive, and have recommended that surgery should be considered only for NFPTs larger than 2-3 cm, while smaller tumors should be carefully surveyed [10,23,24]. Recently, Triponez et al reported that surgery for NFPTs smaller than 2 cm is not beneficial for MEN1 patients, with regard to their life expectancy [25]. On the other hand, a poor correlation between tumor size and malignant behavior has also been documented [26].…”
Section: Discussionmentioning
confidence: 99%